Choline Chloride Mediates Salinity Tolerance in Cluster Bean (Cyamopsis tetragonoloba L.) by Improving Growth, Oxidative Defense, and Secondary Metabolism. Issue 4 (17th November 2021) - Riaz, Saima; Hussain, Iqbal; Ibrahim, Muhammad; Rasheed, Rizwan; Ashraf, Muhammad Arslan
Choline chloride (CC) application enhanced the tolerance of cluster bean ( Cyamopsis tetragonoloba L.) against salinity stress. The aim of the study was to determine the protective role of CC on plant growth, photosynthesis, and biochemical indicators of oxidative stress. The seeds of BR-99 (tolerant) and BR-2017 (sensitive) were surface sterilized and sown in plastic pots containing river sandy soil. The design of the experiments was completely randomized with 4 replicates per treatment. Three weeks after germination, salinity (150 mM) was imposed. Then plants were sprayed with different concentrations of CC (3, 5, and 10 mM), while normal plants were sprayed with distilled water. Salinity decreased growth attributes, relative water contents, photosynthetic attributes, total soluble proteins, total free amino acids, phenolic, flavonoids, ascorbic acid, proline, and glycine betaine and increased the levels of oxidative stress indicators. However, the application of CC (particularly 5 mM) improved growth attributes, photosynthetic pigments, and activities of antioxidant compounds by reducing the levels of H2 O2, malondialdehyde in salt-stressed plants in both cluster bean varieties. BR-99 variety showed more tolerance to salinity stress than that of BR-2017 in the form of greater oxidative defense and osmotic adjustment and clear from greater plant dry masses. Thus, our results showed that the application of CC (5 mM) is an efficient strategy for field use in the areas, where salt stress soils limit agriculture production.